2016
DOI: 10.1128/jcm.02264-15
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Samples Identified as Hepatitis C Virus Genotype 1 without Subtype by Abbott RealTi m e HCV Genotype II Assay Using the New Abbott HCV Genotype Plus RUO Test

Abstract: Hepatitis C virus (HCV) genotyping continues to be relevant for therapeutic strategies. Some samples are reported as genotype 1 (gt 1) without subtype by the Abbott RealTime HCV Genotype II (GT II) test. To characterize such samples further, the Abbott HCV Genotype Plus RUO (Plus) assay, which targets the core region for gt 1a, gt 1b, and gt 6 detection, was evaluated as a reflex test in reference to NS5B or 5′-untranslated region (UTR)/core region sequencing. Of 3,626 routine samples, results of gt 1 without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…While commercial genotyping assays use sub-genomic regions such as core or NS5B in addition to the more conserved 5′ untranslated (5′NC) region, the high genetic variability and small differences between genotypes and subtypes still remain a challenge for both real-time PCR and line probe-based HCV genotyping assays. This also applies to HCV-1 subtyping 1121 . In case of ambiguous results, the use of a second genotyping method may help guiding treatment selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While commercial genotyping assays use sub-genomic regions such as core or NS5B in addition to the more conserved 5′ untranslated (5′NC) region, the high genetic variability and small differences between genotypes and subtypes still remain a challenge for both real-time PCR and line probe-based HCV genotyping assays. This also applies to HCV-1 subtyping 1121 . In case of ambiguous results, the use of a second genotyping method may help guiding treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…However, even this method is not able to resolve every individual sample, e.g. due to failure of amplification 11,13,17,23 . Furthermore, the procedure is considered impractical for most clinical laboratories because it is time-consuming, less sensitive 21 , may be technically challenging, and does not readily allow for detecting mixed-type infections.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study reported among 3626 samples, a rate of 4.7% (171) of genotypes 1 without subtype. Sequencing was applied to 98 of these samples and was successful for 92.9% of the specimen (91/98) …”
Section: Discussionmentioning
confidence: 99%
“…Hence, they developed the Abbott RealTi m e HCV Genotype Plus RUO assay. Recent studies assessed this new add‐on to the HCV genotyping kit, which resolves several indeterminate genotypes 1a, 1b, and 6 …”
Section: Discussionmentioning
confidence: 99%
“…The additional HCV genome targets used for subtyping are in the core region for the Versant HCV Genotype 2.0 and in the NS5B region for the Abbott RealTime HCV Genotype v 2.0. Furthermore, Abbott improved the performance of RealTime HCV Genotype II (targeting the 5′ UTR and NS5B regions), with the ABBOTT Genotype PLUS RUO test, where the core region is used to further characterize genotype 1 unsubtyped samples [7]. Despite the technical improvements in HCV genotyping tools, indeterminate, mixed and unspecified subtype results are obtained in a small but not irrelevant proportion of samples in the daily clinical practice [8].…”
Section: Introductionmentioning
confidence: 99%